1990
DOI: 10.1002/app.1990.070400707
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion copolymers of α‐methylstyrene and styrene

Abstract: SynopsisThe preparation of copolymers of a-methylstyrene and styrene in an emulsion system is described. At both 40 and 60°C, there was no evidence of deviation from simple kinetics. Polymers of high molecular weight and high a-methylstyrene content showed good thermal properties such as TB and softening point. However, these polymers proved to be awkward to process due to a strong proclivity to degrade under shearing conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Error in Variable Methods, 28 introduced into copolymerization reactivity ratio estimations by van der Meer, Linssen, and German, 29 correctly take into account the error in all variables. As mentioned above, experimental monomer conversion versus cumulative copolymer composition 30 or monomer fraction 8,10,29,31,32 data can be used to estimate the reactivity ratios applying the EVM.…”
Section: The Model Should Be Easy To Usementioning
confidence: 99%
“…Error in Variable Methods, 28 introduced into copolymerization reactivity ratio estimations by van der Meer, Linssen, and German, 29 correctly take into account the error in all variables. As mentioned above, experimental monomer conversion versus cumulative copolymer composition 30 or monomer fraction 8,10,29,31,32 data can be used to estimate the reactivity ratios applying the EVM.…”
Section: The Model Should Be Easy To Usementioning
confidence: 99%
“…Kinetic Model. The copolymerization of styrene and α-methylstyrene has been previously studied both in the bulk and in solution. Similarities with the homopolymerization behavior of styrene or α-methylstyrene are often emphasized. The kinetic model of an emulsion polymerization usually divided into three stages is detailed in ref , where different assumptions and subsequent models are discussed.…”
Section: Process Modelmentioning
confidence: 99%
“…This behavior has been variously ascribed to steric restrictions on the placement of successive monomer units (penultimate effect), the reversibility of AMS polymerization, chain transfer to an AMS monomer, and to kinetic factors 5. These kinetic factors include a low propagation rate ( k p = 26 mol/L −1 s −1 ) for AMS homopolymerization 6–11. In earlier studies of the solution copolymerization of the AMS/ST system, Rudin et al reported that the observed slow reaction rates and low MW of polymers probably should be ascribed to the stability of the AMS radical 12, 13.…”
Section: Introductionmentioning
confidence: 99%